The Influence of Christian Work Ethic and Mapalus Management on the Work Productivity of Farmers' Groups in Mopolo Village, Ranoiapo District - Sembung, Josua G.; Mamahit, Meyke M.; Weol, Wolter (International Journal of Education, Information Technology, and Others, 2024)
This research aimsed to determine the influence of the Christian Work Ethic on Work Productivity, to determine the influence of Mapalus Management on Work Productivity and to determine the influence of the Christian Work Ethic and Mapalus Management together on Work Productivity. This research used a quantitative approach with a causal associative method. The total population in this study was 203 people and the number of samples taken was 66 people. The sampling technique in this research was is engineering probability sampling namely by using sampling techniques stratified random sampling. The findings of this research showed that: 1) there was a positive influence of the Christian Work Ethic variable (X1) on the Work Productivity variable (Y), 2) there was a positive influence of the Mapalus Management variable (X2) on the Work Productivity variable (Y), 3) there was an influence positive variable Christian Work Ethic (X1) and Mapalus Management (X2) together on the Work Productivity variable (Y). With a high work ethic and the implementation of mapalus-based management functions in farmer groups, it can have an impact on increasing work productivity